Tracing Social Movements' Influence Beyond Agenda-Setting: Waves of Protest, Chaining Mechanisms and Policy Outcomes in the Chilean Student Movement (2006-2018) - Bidegain, Germán; Maillet, Antoine (PARTECIPAZIONE E CONFLITTO, 2021)
The literature on social movements' policy outcomes agrees on the need for an intertemporal perspective that goes beyond a short-term action-reaction logic to account for the effects of mobilization on policies. However, little attention has been given to the causal mechanisms that link different waves of mobilization with related policy outcomes over time. To do so, we propose the concept of chaining mechanisms as a means to connect different iterations of protest, electoral cycles and policy responses within a mid-term perspective. We distinguish between two types of chaining mechanisms, strategic and inertial, and apply this conceptual framework to the Chilean student movement in the 2006 and 2018 period. We assert that its success in chaining different waves of protest is a crucial factor in accounting for the recent major education reform that took place under Bachelet's government (2014-2018). Beyond the case, the concept contributes to the understanding of the complex interactions between social mobilization and public policy.